Autoantibodies targeting nephrin in podocytopathies - Hengel, Felicitas Eugenia; Dehde, Silke; Lassé, Moritz; Zahner, Gunther; Seifert, Larissa; Schnarre, Annabel; Kretz, Oliver; Demir, Fatih; Pinnschmidt, Hans O.; Grahammer, Florian; Lucas, Renke; Mehner, Lea Maxima; et al. (The New England journal of medicine, 2024)
Antinephrin autoantibodies occur in adults with minimal change disease and children with idiopathic nephrotic syndrome and appear to be disease activity markers. Their binding at slit diaphragms may induce podocyte dysfunction.